Implikasi Penolakan Akta Notaris Pasca Penandatanganan Akta oleh Klien (Lembaga Pengembangan Kinerja Dosen, 2025)
Notarial deeds are authentic evidence that have perfect evidentiary power in the legal process. However, in practice, there is a phenomenon where clients reject deeds that they have signed before a notary. This rejection raises legal issues regarding the validity of the deed, the notary's responsibility, and legal protection for the parties. This article aims to examine the legal implications of the rejection of a deed by a client after signing, as well as to examine efforts to resolve disputes that may arise. This study uses an empirical legal approach by collecting data through interviews with notaries and case studies in certain areas. The results of the study indicate that rejection of a deed after signing can cause legal uncertainty, and requires notaries to be careful in the process of making and reading the contents of the deed to the parties. Strengthening standard operating procedures and legal education for the public is needed to prevent similar disputes in the future.